Saberes e conhecimentos necessários ao diretor de escola para a implementação da gestão participativa - Oliveira, André Dias de (2021)
Nowadays, we observe the growing demand for the participation of citizens in society, and also of the community in public schools, especially after the process of democratization of teaching, with the advent of the Federal Constitution of 1988. The thematic about participation has been gaining prominence in the discussions of the contemporary school because it is considered an essential means to promote the democratization of the public education sector. Intending to think about participative management in the context of education, we start from the guiding question: what is the knowledge needed by the school principal for the implementation of participative management? To answer this question, we present as our objective: to analyze the knowledge needed by the school principal for the implementation of participative management. This research was carried out in the context of the state public institutions of elementary and high school administered by the Directorate of Education North 2, located in the north of the capital of São Paulo. The surveyed participants were three school principals, who exercise their functions in schools of the Directorate of Education North 2. The research approach was qualitative, and we used document analysis, especially Resolution SE 56/2016 (SÃO PAULO, 2016), and semi-structured interviews with the three principals as methodological procedures. Our theoretical framework is composed by the following authors: Luck (2006), Libâneo (2005), Severino (1992), Freire (2007), Demo (2001), Paro (2000), Imbernón (2011), Tardif (2002), among others. As a result of the research, the principals indicate that, in the training for school managers, some important dimensions must be considered in the context of their action, such as the mechanisms for building participative management, based on the sharing of responsibilities, and the articulation with collegiate bodies: Councils, Parents and Teachers Association and Student Union. They also mention necessary requirements for the implementation of participative management, such as humanization in the school space, the development of dialogue with the school and local community, the strengthening of the culture of belonging, the construction of collaborative work and the resolution of conflicts, so that everyone feels part of the school and actively participates in decision-making and actions in the school and society